ANALISIS KESULITAN SISWA SMK KELAS X DALAM MENYELESAIKAN SOAL MATERI BENTUK AKAR - Irpan Muhammad Yusuf; Gida Kadarisma; Tina Rosyana (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
Problems in learning mathematics that are often encountered include the inability of students to understand correctly the subject matter being taught resulting in the achievement of student learning outcomes being less than optimal. The purpose of this study was to describe the results of the analysis of the difficulties of class X SMK students in solving root form problems. The research method used in this study is a qualitative descriptive method. The subjects of the study were 13 students of class X at SMK 4 LPPM RI. The research instrument consisted of three root form test questions. The data collection technique used in this study was in the form of test results. The results of the study indicate that students' mastery of the material is above 70% so it can be said that students have no difficulty in solving problems. However, students still have difficulty understanding the concept of root form and errors in calculations. From the results of the analysis, it can be concluded that class X SMK students in solving root form problems in calculating the final settlement, while for indicators determining the concept of rationalizing root forms, it is above 70%.